Supplier selection in the construction material purchasing function - Samarasinghe, DAS; Tookey, JE; Rotimi, J.O.B.; Thiruchelvam, S (World Business Institute (WBI), 2012)
Construction materials occupy a significant part of the construction’s value contributing nearly 50%. Thus when selecting construction materials, it is very important that painstaking decisions should be made. Past literature and anecdotal evidences show that the main issue with building materials purchasing comes with supplier selection, and depend on careful examination of supplier economics among other criteria. Supplier selection is the purchasing function that forms the foundation for the success or failure of projects. Therefore supplier selection criteria should be well defined. Supplier selection is a multi-criteria decision making problem which includes both qualitative and quantitative considerations. A trade-off between tangible and intangible criteria is important in selecting the best supplier. This paper presents a review of supplier selection processes and decision making methods reported in academic and other literature related to the construction industry. The study is a part of an on-going doctoral research study on construction material purchasing decisions aimed at determining how small to medium scale (SME) construction contractors could secure ‘best prices’ for their key material inputs in New Zealand construction industry. This is a first step towards a comprehensive empirical study of securing best construction material prices.